ANTIOXIDANT ACTIVITY OF THE ACTIVE FRACTION OF MANGOSTEEN RIND EXTRACT (GARCINIA MANGOSTANA) - WIDAYANTI, ARI; JUFRI, MAHDI; SURINI, SILVIA; ELLYA, BERNA (International Journal of Applied Pharmaceutics, 2024)
Objective: Determination of the IC50 value of the active Fraction was carried out to see the antioxidant activity of the ethanol extract of mangosteen peel (Garcinia mangosteen) Mangosteen peel is known to have very strong antioxidant activity. The research began with maceration of mangosteen peel with ethanol solvent. Then, the mangosteen peel extract was fractionated with three solvents, namely those with different polarities, namely water, dichloromethane, and n-hexane. Methods: The ethanol extract of mangosteen rind was further fractionated using n-hexane, dichloromethane, and water, then the solvent was removed by evaporation. The three resulting fractions were measured for antioxidant activity using the DPPH method with Quercetin as a comparison. The active Fraction with the highest IC50 value is then compared with the extract, and the comparison is seen with TLC. Next, the Fraction was tested with GC to see the remaining solvent. And then continued with determining alpha mangostin levels in all fractions using UHPLC. Results: IC50 value for each n-hexane fraction was 50.65µg/ml, the dichloromethane fraction was 34.66µg/ml, and the water fraction was 45.72µg/ml. The results of the solvent test showed that there was no residual solvent in the dichlormethane fraction, as seen from the chromatogram results. The results of the assay showed the following results: n-Hexan fraction 25.18%, DCM fraction 31.23%. Conclusion: The dichloromethane fraction showed the highest antioxidant activity with the best IC 50 value and had higher levels of alpha mangostin than the water and n-hexane fractions.